2017
DOI: 10.1063/1.4982032
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the memory state of floating gate transistors with repeated femtosecond laser backside irradiations

Abstract: We demonstrate that infrared femtosecond laser pulses with intensity above two-photon ionization threshold of crystalline silicon (c-Si) induce charge transport through the tunnel oxide in floating gate Metal-Oxide-Semiconductor (MOS) transistor devices. With repeated irradiations of Flash memory cells, we show how the laser-produced free-electrons naturally redistribute on both sides of the tunnel oxide until the electric field of the transistor is suppressed. This ability enables to determine in a nondestruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…It can thus be concluded that the only consequence of individual laser shots, after thermodynamic equilibrium is reached again, lies in a change of the floating gate charge and the potential distribution in the vertical direction of the injection zone. In our previous works 18,19 no damage of the tunnel oxide (surface or volume) has been observed, even at laser energies much higher than the ones employed in this study. This can indicate the effect of Anode Hole Injection (AHI) can here be neglected, especially since the biases applied on the Control Gate (and thus on the Floating Gate) are low.…”
Section: Resultscontrasting
confidence: 41%
See 4 more Smart Citations
“…It can thus be concluded that the only consequence of individual laser shots, after thermodynamic equilibrium is reached again, lies in a change of the floating gate charge and the potential distribution in the vertical direction of the injection zone. In our previous works 18,19 no damage of the tunnel oxide (surface or volume) has been observed, even at laser energies much higher than the ones employed in this study. This can indicate the effect of Anode Hole Injection (AHI) can here be neglected, especially since the biases applied on the Control Gate (and thus on the Floating Gate) are low.…”
Section: Resultscontrasting
confidence: 41%
“…This last equation, when combined with Eqs (5) and (6), allows a deeper understanding of the experimental results displayed in Figs 4 and 5. At a given laser intensity, and considering the fact that | V FG | = f (| V CG |) is an increasing function (see supplementary material of our previous work 19 ), the oxide electric field and thus the transmission coefficient of tunneling electrons will be enhanced as | V CG | gets higher. These considerations should explain why, as seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations